Water Quality, Perception And Consumer’s Satisfaction Towards Domestic Water Filters - Mat Salleh, Roslina (2007)
Water is the most crucial source for the continuity of all creatures on earth. Thus, water safety issue becomes very important. Consumer’s complaints and reports from related government departments show that consumers are not satisfied with the quality of water supplied. A large number of consumers decided to treat the water using domestic water treatment systems. The objectives of this study are to determine the quality of water supplied to homes and to study the level of knowledge, perception, practice and consumer’s satisfaction towards water quality and the filtering system used in their homes. A survey was carried out involving 135 respondents in Bandar Baru Bangi, Selangor Darul Ehsan. Water samples from taps, tanks and water filters were taken from 27 premises to be tested for their free chlorine content, total coliform, turbidity, conductivity, pH, ammonia nitrogen, iron, temperature and dissolved oxygen. The results showed that almost all respondents (98.52%) experienced problems with the water supplied to their homes with the perception that its quality was not satisfactory and had the impression that the water could harm their health. The majority of the respondents viz 76.1% had a low level of satisfaction towards the water supplied and 83% felt that the water filter system provided benefits to them.The results also showed that unfiltered water quality was generally better than the filtered water, but the respondent’s satisfaction was higher for filtered water compared to unfiltered water. In conclusion, the respondents satisfaction towards water was not influenced by the actual quality of the water. The result of this study suggests that some action should be taken so that consumers are aware of the real situation. Researchers can do further studies to assist government and consumers in drinking water consumption. Manufacturers and sales persons should be more responsible in marketing their products since it can affect the health of consumers.